INDUCTION OF POLYPLOID BANANA KEPOK THROUGH IN VITRO ADDITION OF FLAME LILY EXTRACT - Eti Ernawiati; Lili Chrisnawati (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Flame lily (Gloriosa superba L.) contains colchicine and gloriosin in almost all parts of the plant, especially in tubers and seeds. Colchicine is often used in biological and breeding studies to induce mutations that result in polyploid plants. This study aimed to examine the effectiveness of flame lily tuber extract as a natural mutagen for the development of superior kepok banana cultivars through the in vitro assembly of polyploid kapok bananas. The study was arranged completely randomly with two factors. Factor 1 consisted of 3 levels, namely fresh extract of breech flower tubers (10 %), pure colchicine solution (0.1%) as a positive control, and without being added (0%) as a negative control. Factor 2 consists of 3 levels, namely Kepok Abu, Kepok Batu and Kepok Kuning. All treatment combinations were repeated 5 times. The data were analyzed by Diversity Test (Sidik Ragam) and if there is a difference, it will be continued with the DMRT test at a level of 5%. The results showed that the administration of colchicine in culture media could induce the emergence of polyploid banana plantlets when viewed from the addition of the size of the number of shoots, shoot length, number of roots, root length, leaf area, epidermal cells, stomata, and decreased stomata index. Meanwhile, 10% breech flower tuber extract was not able to induce the emergence of polyploid plantlets. Kepok Kuning bananas had a better response to mutagens than Kepok Abu and Kepok Batu. From these results, it can be concluded that 0.1% colchicine was able to induce polyploid banana plantlets and 10% breech flower tuber extract was not able to induce polyploid plantlets.